Le fléchois Jérôme le Royer de La Dauversière et l'utopie de Montréal - Oury, Guy-Marie (La Province du Maine, 1983)
Tome: Tome 4
Keywords: Le Royer de La Dauversière, Jérôme

The Beginnings of a Society: Montreal, 1642-1663 - Trudel, Marcel (Economy and Society During the French Regime, to 1759, 1983)

La fondation de Montréal et la piété des Champenois - Zuber, Roger (La vie à Troyes sous Louis XIII, journées d'études, 1983)